2022
DOI: 10.1186/s12891-022-05198-9
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine combined with ropivacaine for erector spinae plane block after posterior lumbar spine surgery: a randomized controlled trial

Abstract: Purpose Due to lumbar spinal surgery is frequently accompanied with moderate-to-severe postoperative pain, it is necessary to find an effective postoperative analgesia for patients with this surgery. This study aimed to observe the analgesic effect of dexmedetomidine combined with ropivacaine erector spinae plane block (ESPB) used in posterior lumbar spine surgery. Methods In this clinical trial, patients undergoing posterior lumbar spine surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…A sensitivity analysis was conducted to examine the source of heterogeneity. The pooled analysis results remained unchanged after excluding the data of Wang YH et al [ 25 ], but the heterogeneity was low (MD = -5.79; 95% CI = -7.24 to -4.35; p < 0.00001; I 2 = 0%; random-effects model; Fig. 5 ), indicating that this study is the main source of heterogeneity.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…A sensitivity analysis was conducted to examine the source of heterogeneity. The pooled analysis results remained unchanged after excluding the data of Wang YH et al [ 25 ], but the heterogeneity was low (MD = -5.79; 95% CI = -7.24 to -4.35; p < 0.00001; I 2 = 0%; random-effects model; Fig. 5 ), indicating that this study is the main source of heterogeneity.…”
Section: Resultsmentioning
confidence: 82%
“…Four RCTs reported the number of PCIA presses within 72 h after the operation. The pooled analysis showed that DEX as adjuvants significantly reduced the number of PCIA presses (four studies [ 19 , 21 , 22 , 25 ]: MD = -4.12; 95% CI = -7.79 to -0.45; p = 0.03; I 2 = 93%; random-effects model; GRADE = Low; Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations